Analisis Fasa Sistem Mn(1-X)NdxFe2O4 sebagai Kandidat Bahan Penyerap Gelombang Mikro [Phase Analysis of Mn(1-x)NdxFe2O4 System as Candidate of Microwave Absorber Materials] - Yunasfi; Rachmawati, Indri; Mashadi; Adi, Wisnu Ari; Arofah, Nurmaya (Jurnal Metalurgi, 2018)
Phase analysis of Mn(1-x)NdxFe2O4 system as candidate of microwave absorber materials have been carried out. Mn(1x)NdxFe2O4 (with x = 0.0; 0.1 dan 0.2) system was synthesized by mixing the powder of Fe(NO3)3, Mn(NO3)3 and Nd(NO3)3 in mole ratio. The mixture was dissolved with ethyleneglycol, dried at 120C and sintered at 1200C for 3 h. Phase identification with XRD (x-ray diffractometer) shows that multiphase have been formed which is indicated by the appearance of MnFe2O4 and NdFeO3 phase. According to the morphological observation with SEM (scanning electron microscopy), it is known that all of the samples has unhomogeneous structure with particle size is 200-400 nm. The results of microwave absorbing properties measured by VNA (vector network analyzer) shows that the increasing substitution of Nd3+ ion will increased the ability of material to absorb microwave with the highest value of ~93% for the composition of x=0.2 (Mn0.8Nd0.2Fe2O4).